Human experience and place : sustaining identity - Brislin, Paul. (Hoboken, N.J. : Wiley ; Chichester : John Wiley [distributor], 2012)
Exceptional architecture stands in the face of the negative aspects of commercial globalisation by celebrating the spirit of individual place; and by being rooted in its culture, its geography and in the experience and value systems of the people that have created it. By drawing from work across the world, this issue of AD will demonstrate that it is possible for architects, designers and engineers to design outstanding buildings that sustain a sense of local identity, both in terms of cultural heritage and the conservation of the environment. In the last few years, a groundswell of critical resistance to the homogenised imposition of a form-driven universal architecture, which defies local context, has continued to grow unabated, as has developing interest in an alternative pathway to the design of buildings. Human Experience and Place will be launched at the third 'Sustaining Identity' symposium at the V&A in London in November 2012, curated by Paul Brislin and Juhani Pallasmaa and co-partnered by Arup Associates, the V&A and Architectural Design; and featuring contributors to the issue. 'Sustaining Identity' gathers likeminded exemplary practitioners of an architecture of resistance together on a biannual basis: an alternative avant-garde whose work sustains human identity through its focus on specific culture and place.
Selected conference papers.
"November/December 2012."
Includes bibliographical references.
Keywords: Architecture and society -- Congresses; Architecture -- Human factors -- Congresses